The Philosophy of Local History of Kajaolaliddong - Akkase Teng, Muhammad Bahar (International Journal of Supply Chain Management, 2020)
Abstract- This research aims to analyze the Supply chain management in economy development, which is conducted using secondary sources, in addition to primary sources in the form of data from informants domiciled in Bone Regency. This research is also conducted to find out about Economy development as a role model who are honest, intelligent, and brave. Economy development is known as a scholar, statesman, and a reliable diplomat, whose thoughts became the concept of pangadereng, which then metamorphoses into a basic pattern of royal government. Supply chains are increasingly becoming more complex and dynamic. The success of any business often depends on the success of its supply chain activities. Supply chain management solutions and services help manage and optimize the many facets of supply chain planning, sourcing procurement, inventory optimization, warehouse management, logistics distribution transportation and supply chain integration.